Análise do processo de julgamentos contábeis por discentes concluintes do curso de Ciências Contábeis - Lima, Aldo Novaes (2019)
With the convergence of Brazilian accounting standards to international accounting standards, Brazil now has a normative system based essentially on general principles. One of the main features of this regulatory system is the greater scope for the accounting professional to act on the judgment of the accounting information reported in the financial accounting reports. With a view to supporting teachers in teaching principles-based rules, Wells and Tarca (2014a; 2014b; 2014c), within the IFRS Foundation, suggest teacher support material for the development of skills for the progressive teaching of judgments in accordance with IFRS. This study aimed to know and analyze the confidence level of students in the last year of the Financial Accounting undergraduation course in view of the need to make accounting judgments. The present study was exploratory and descriptive and used a quantitative method regarding the statistical analysis of the data collected through the application of a questionnaire containing 5 accounting cases related to accounting judgments. The questionnaire was applied to 174 graduating students of the Financial Accounting undergraduation course in the city of São Paulo, represented by 12 universities grouped in 4 intervals according to their performance in the result of the 2nd edition of CFC (Federal Council of Accounting, initials in Portuguese) of 2017. Based on the responses, a statistical analysis of the association of correct and incorrect answers was made in relation to the judgments made using Pearson's chi-squared test and analysis of variance (ANOVA) for comparison of confidence level averages to make accounting judgment. Regarding the success of judgments in accordance with IFRS, it was observed that students of IES in the range 1 |--10 were those that stood out in the accounting scenarios 1 (Asset Recognition), 2 (Asset Measurement) and 4 (Recognition of Liabilities). However, it was the students of IES in the range 11 |--20 who were most confident in making accounting judgments related to Case 1 (Asset Recognition), Case 3 (Revenue Disclosure) and Case 4 (Liability Recognition). By Pearson's chi-square test (at a significance level of 0.05) for comparing hits and misses between IES intervals, the results suggested significant differences for Case 2 (Asset Measurement) and Case 4 (Recognition of Liabilities), indicating critical topics to be best addressed in the classroom. By the ANOVA of the mean confidence level (95% confidence interval inference), the results suggested significant differences, with a higher positive highlight for IES in the 11 |--20 range when compared to IES in other ranges. For Case 1 (Asset Recognition) students in range 11 |--20 had a higher level of confidence than students in range 21 |--30 and for Case 2 (Asset Measurement) students in range 11 |--20 had a higher level of confidence than students in the range 21 |--30. It was possible to observe an inadequate understanding of what is the adoption of principles-based rules, making the student define the system by the rules. In addition, were realized that the level of confidence declared by the student was not always supported by adequate IFRS technical knowledge. The use of IFRS teaching methodology that encourages student autonomy to make judgment on financial information in solving real-life problems is a valuable method for academic teachers to develop professional skills related to accounting judgment under IFRS